2008
DOI: 10.1007/s11469-008-9154-4
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Adverse Events and Health Outcomes Among Methamphetamine-Dependent Men and Women

Abstract: To describe the prevalence of childhood adverse events (CAEs) among methamphetamine-dependent men and women, and assess the relationship of cumulative CAEs to health problems. Data for 236 men and 351 women were analyzed assessing CAEs. Dependent variables included 14 self-reported health problems or psychiatric symptom domains. Mental health was assessed via the Mini-International Neuropsychiatric Interview. Medical conditions were collected using the Health Status Survey. Women reported more cumulative expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Mental health professionals and prison administrators who work with incarcerated females must be aware of these statistics, particularly in light of research exploring the influence of victimization on the victim's life after the event (e.g., Ireland & Widom, 1994;Malinosky-Rummell & Hansen, 1993;McClellan, Farabee, & Crouch, 1997;Messina et al, 2007;Mullings, Hartley, & Marquart, 2004). Among females who are incarcerated or abuse substances in particular, victimization and trauma during childhood have been linked to medical and mental health problems during adulthood (Messina et al, 2008;Messina & Grella, 2006).…”
Section: Victimization Among Prisonersmentioning
confidence: 99%
“…Mental health professionals and prison administrators who work with incarcerated females must be aware of these statistics, particularly in light of research exploring the influence of victimization on the victim's life after the event (e.g., Ireland & Widom, 1994;Malinosky-Rummell & Hansen, 1993;McClellan, Farabee, & Crouch, 1997;Messina et al, 2007;Mullings, Hartley, & Marquart, 2004). Among females who are incarcerated or abuse substances in particular, victimization and trauma during childhood have been linked to medical and mental health problems during adulthood (Messina et al, 2008;Messina & Grella, 2006).…”
Section: Victimization Among Prisonersmentioning
confidence: 99%
“…Childhood and family adverse events are also associated with more drug abuse problems in Iran and other countries (5860). Drug abuse is also reported in association with impulsivity (30) and delinquent antisocial behaviors in Iran (22) as well as other countries (6164).…”
Section: High School Studentsmentioning
confidence: 99%
“…For example, longitudinal studies have shown that females are more likely to experience sexual abuse (Ompad et al, 2005; Wang et al, 2010), with many females experiencing multiple forms of maltreatment (Messina et al, 2008; Wang et al, 2010) whereas males experience physical abuse (Wang et al, 2010). In cross-sectional studies, there is also evidence of gender differences in the experience of specific (Kang, Deren, & Goldstein, 2002; Lake et al, 2015; Markowitz et al, 2011; Shand, Degenhardt, Slade, & Nelson, 2011) and multiple (Wu et al, 2010) forms of childhood maltreatment in injecting drug users.…”
Section: Introductionmentioning
confidence: 99%